Breakthrough invasive fungal infections in liver transplant recipients exposed to prophylaxis with echinocandins vs other antifungal agents: A systematic review and meta‐analysis. Issue 11 (23rd August 2021) - Gatti, Milo; Rinaldi, Matteo; Ferraro, Giuseppe; Toschi, Alice; Caroccia, Natascia; Arbizzani, Federica; Raschi, Emanuel; Poluzzi, Elisabetta; Pea, Federico; Viale, Pierluigi; Giannella, Maddalena
Abstract: Introduction: Although echinocandins are recommended as first‐line prophylaxis for high‐risk orthotopic liver transplant (OLT) recipients, occurrence of breakthrough‐invasive fungal infections (IFIs) remains a serious concern. We aim to assess the risk of breakthrough IFIs among OLT recipients exposed to prophylaxis with echinocandins compared to other antifungals. Materials and methods: Two authors independently searched PubMed‐MEDLINE, Embase, study registries and reference lists from inception to March 2021, to retrieve randomised controlled trials (RCTs) or observational studies comparing efficacy and safety of echinocandins vs other antifungals for prophylaxis in OLT recipients. Data were independently extracted from two authors, and the quality of included studies was independently assessed according to ROB 2.0 tool for RCTs and ROBINS‐I tool for observational studies. The primary outcome was occurrence of breakthrough IFI at the end of prophylaxis (EOP). Results: 698 articles were screened, and ten studies (3 RCTs and 7 observational) were included. No difference between echinocandins and other antifungals in terms of breakthrough IFIs at the EOP emerged both from RCTs (odds ratio [OR] 0.85, 95% CI 0.24–2.99) and observational studies (OR 1.43, 95% CI 0.28–7.40). No difference emerged also for secondary outcomes. In the subgroup comparison between echinocandins and polyenes, a trend for higher risk of breakthrough IFI at the EOP (OR 4.82, 95% CI 0.97–24.03) was noted. Conclusions: Echinocandins do not seem to be associated with increased risk of breakthrough IFIs in OLT recipients. However, the large diversity in the comparator group hinders a definitive interpretation. Further studies exploring the relationship between echinocandin use and breakthrough IFIs according to specific comparators are warranted.